Malaysia Economic Monitor, June 2014 : Boosting Trade Competitiveness - World Bank (Bangkok, 2014)
This economic update provides an overview for 2013 and early 2014 in Malaysia and an analysis of structural trends in trade competitiveness. The economy overcame a weak start in 2013 to experience GDP growth through 2014. The improved performance was driven mainly by a recovery in exports, including of the long-ailing electrical and electronics sector. The outlook remains favorable and GDP is expected to continue growing through 2015. Growth will be sustained by positive external conditions, with foreign demand outweighing headwinds in domestic demand. Investment and imports of capital goods will remain robust as large projects move forward. Medium-term fiscal consolidation remains on track and the debt-to-GDP ratio has stabilized, but additional spending measures are needed for the Government to meet its 2014 deficit target. The central bank has signaled that it may have to tighten policy to avoid the build-up of financial imbalances. Labor markets are healthy, and Malaysia has enjoyed higher employment levels, real wage gains, and higher labor incomes. External risks to the economic outlook have receded, but the high share of Malaysia's foreign debt means it is sensitive to international volatility. Boosting exports to fully leverage the improved external environment will be critical for sustained growth. The report's analysis of Malaysia's trade competitiveness focuses on its ability to grow exports and the domestic value-added. Malaysia's exports had been faltering since before the Global Financial Crisis. The core electrical and electronics sector declined in the 2000s, and Malaysia's domestic value-added is relatively low due to limited domestic linkages. Exports of services have also lagged and remain an area of significant potential. Restrictive Government policies play a role in hindering export growth, although the Government has recently embarked on a liberalization of service sectors. Improving domestic value-added tasks will require addressing skill gaps. Finally, Malaysia's upcoming chairmanship in ASEAN offers concrete avenues to boost trade competitiveness.